Plasma and brain cholinesterase in methomyl-intoxicated free-ranging pigeons (Columba livia f. domestica) (2010)
ABSTRACT: A mortality event caused by exposure to the carbamate insecticide methomyl was diagnosed in several hundred pigeons fed treated corn kernels in a city park. A cholinesterase inhibitor insecticide was initially suspected based on clinical signs and a significant inhibition (P < 0.05) of brain cholinesterase (ChE) activity compared with normal values for the species. However, brain ChE activity was within the normal range in birds subsequently submitted in an advanced stage of autolysis. Two groups of 10 healthy pigeons were allocated into a control group and an experimental group, which was offered corn samples retrieved from the incident site. Within minutes of ingesting the contaminated corn, the birds became immobile, had transient wing fluttering, and developed profuse salivation immediately followed by death. Plasma ChE activity at death had declined by more than 95% of preexposure levels (0.04 +/- 0.02 vs. 1.56 +/- 0.23 micromol/min per milliliter). Brain activity in the sagittal brain sections that were immediately frozen after death was inhibited by > or =50% of control birds (13.5 +/- 2.2 vs. 27.5 +/- 1.8 micromol/min per gram). However, the sagittal sections left for 1.5 days at ambient temperature of 25 degrees C had normal or higher activity, an effect that was attributed to a combination of spontaneous reactivation and dehydration. After incubation of both plasma and brain homogenates for 1 hr at 37 degrees C, ChE activity recovered by 2- and 1.46-fold, respectively. An organophosphorus and carbamate screen conducted by 2 independent laboratories identified and quantified methomyl in treated kernels at 400 ppm. These results indicate that spontaneous reactivation and dehydration can mask previous reductions in ChE activity.